Mind the Gap! Sleep Problems in Children With ADHD—A Qualitative Analysis of Clinician Training Needs. - Smith, Lucy; Daley, David; Cortese, Samuele; Hill, Catherine M. (Child: Care, Health & Development, 2026)
Background: This study aims to explore for the first time the knowledge, understanding and management of sleep problems in children with ADHD among clinicians who specialise in sleep and ADHD. The aim was to inform the development of digital sleep awareness training for clinicians. Method: Fifteen clinicians who work with children with ADHD and sleep difficulties in the United Kingdom participated in semistructured qualitative interviews. Data were analysed using a reflexive thematic analysis approach to generate and guide the content of digital sleep awareness training. Results: Four core themes were developed: 'It's a Problem' highlighted the extent to which children with ADHD were reported to struggle with sleep difficulties and the impact this has on the child and family. Clinicians also discussed the difficulty they had in finding evidence‐based information they could share with caregivers. With little to no formal training, most of the advice they gave came from 'learning on the job'. When discussing ADHD specific sleep difficulties and disorders, clinicians reflected on their own 'insight into limitations of knowledge'. 'Learning for practice' highlighted the divergence in the methods of learning preferred by clinicians, despite convergence of learning content needed. Conclusions: Sleep problems in children with ADHD are common, and clinicians often struggle to support these due to lack of formal training. There is a need for accessible, authoritative training for UK practitioners who work with children with ADHD. Summary: When asked about their training needs on advising and supporting families of children with ADHD and sleep difficulties, clinicians confirm that sleep difficulties are a problem.Clinicians report that due to a lack of formal training, they often have to learn on the job and highlight limitations to their knowledge on sleep.Clinicians suggest that future training needs to be briefly delivered in bite‐sized sessions, probably in a digital format and from a trusted source.Lack of knowledge on sleep may lead to diagnostic over‐shadowing as well as confusion about ADHD risk versus risks associated with sleep problems.